Pengaruh Terapi Bermain Mewarnai Gambar terhadap Kecemasan Hospitaslisasi pada Anak Prasekolah - Dwi Aryani; Nedra Wati Zaly (Jurnal Akademika Baiturrahim Jambi, 2021)
Hospitalization is a state of crisis in children, when the child is sick and hospitalized. The hospital care environment can cause fear and anxiety in the child. Play activity therapy is one of the good activities to overcome the anxiety of children who are hospitalized, so that it can accelerate the healing process of pain in children. This study aims to find out the effect of play therapy coloring pictures on anxiety due to hospitalization in preschool age children in the pavilion of Gatot Soebroto Hospital. This research applies pre-experimental method with one group pre test post test design approach. The sample of this study was 35 respondents with purpose sampling techniques. T test results obtained p = 0.000 value if α = 0.05 then p<α and Ha are accepted. The results of this study showed that there is an influence of play therapy coloring pictures on the decrease in anxiety due to hospitalization in preschool-age children in the Pavilion of Gatot Soebroto Hospital in 2019. This research is expected to increase play therapy activities as one of the interventions to help reduce anxiety, especially preschool-age children who are experiencing hospitalization